Synthetic Rice Genome and Epigenetic Engineering: Emerging Strategies for Climate-Resilient Crops: Review Article - Rouya Ahmed; Raghda Sultan (Journal of Health and Biology, 2026)
Rice (Oryza sativa) is among the most important staple food crops in the world, serving as a main source of food security for approximately one-half of the world's population. Nevertheless, its cultivation is becoming compromised due to climate change, as repeated drought and saline soils, along with erratic temperatures, pose heavy restrictions on its yield. Traditional breeding and genetic engineering have contributed to enhancing crop performance; however, they are still constrained by the complex stress-responsive networks and by the time taken to develop tolerant cultivars. In order to overcome these challenges, technologies on the horizon, synthetic genomics and epigenetic engineering, are becoming game-changers in crop science. Synthetic genomics permits the refactoring and partial reassembly of plant genomes, thereby allowing new gene circuits to be built in, synthetic chromosomes to be installed, and multiplex editing via CRISPR-mediated alterations to increase drought tolerance or salinity resistance or boost photosynthesis in rice. Concurrently, epigenetic changes such as DNA methylation and histone modification, as well as non-coding RNA-mediated regulation, can impose a more dynamic and reversible layer of control on gene expression by modulating stress responses while leaving the actual DNA sequence unaltered. Emerging evidence indicates that certain epigenetic marks are capable of being 'remembered' across generations and could influence long-term resilience to stress. This review emphasizes the use of synthetic genomics-based epigenetic regulation as a new horizon in climate-resilient rice improvement.